PELATIHAN STRATEGI BRANDING UNTUK PENGEMBANGAN EKONOMI KREATIF BERBASIS KEARIFAN LOKAL - Abednego Priyatama; Supiani; Ardhy Lazuardi; Abdul Rahman Agung Ramadhan; Nugroho, Eko Aprianto; Natallios Peter Sipasulta (Jurnal Abdi Masyarakat Multidisiplin, 2024)
This Community Service Program aims to provide training on branding strategies for developing creative economies based on local wisdom. Conducted by Universitas Gunadarma in collaboration with the Young Indonesian Lecturers Association (ADMI), the program utilizes a multidisciplinary approach encompassing 10 fields of study, such as management, engineering, and communication. The training integrates theory and practice, leveraging information and communication technology (ICT) to support local entrepreneurs in maximizing their cultural and local potential. The program enhances the competitiveness of local products through strong brand identities, digital marketing strategies, and the development of soft skills such as creativity, adaptability, and collaboration. Through simulations and real-world case studies, participants are guided to design, test, and evaluate their branding strategies. The expected outcomes include improved local brand quality, growth of the creative economy, and strengthened cultural identity, which positively impact the sustainability of regional economies.